Integrating Staggered and Collaborative Learning for Ethical AI-Assisted Academic Writing (Program Studi Pendidikan Teknologi Infromasi UMK, 2025)
The rapid advancement of artificial intelligence (AI) has prompted a paradigm shift in higher education, demanding innovative instructional models that not only leverage technological tools but also foster ethical, critical, and adaptive thinking among students. This study explores the implementation of a staggered and collaborative learning approach for teaching AI-assisted academic writing in the Software Measurement and Quality course at Universitas Ma Chung. The instructional design began with the formation of small student groups, followed by a structured introduction to generative AI tools—such as ChatGPT Plus and Consensus—paired with discussions on ethical use, fact-checking, and reference validation. Rather than emphasizing technical details, the concept of prompt engineering was taught as a set of adaptable, strategic principles, enabling students to construct effective prompts as technology evolves. Through staggered, step-by-step activities, students were guided from initial brainstorming and article drafting to in-depth literature reviews and iterative revision, with each group collaborating internally and across teams to share references and insights using tools like Mendeley Reference Manager. The lecturer’s ongoing formative feedback, combined with originality checks via Turnitin, ensured both academic integrity and continuous improvement. At the end of the process, students submitted their articles to designated journals and completed a feedback questionnaire. The analysis of student responses revealed overwhelmingly positive outcomes: nearly all participants reported a clearer understanding of course objectives, increased motivation, and greater creativity. Students highlighted the ease and effectiveness of AI tools in supporting their research, the value of collaborative reference sharing, and the importance of ethical AI practices. The majority also recognized that prompt engineering requires strategic, iterative approaches rather than fixed formulas. In conclusion, the findings demonstrate that the staggered and collaborative learning model not only enhances academic writing skills and ethical awareness but also prepares students for lifelong learning and responsible technology use in an AI-driven academic landscape.